Phase change in spiral coil heat storage systems. (April 2018) - Ahmadi, R.; Hosseini, M.J.; Ranjbar, A.A.; Bahrampoury, R.
Highlights: Melting process of a PCM in a spiral coil tube system is numerically studied.‎Melting process of a PCM in a spiral coil tube system is numerically studied.‎ Spiral coil diameter has great influence on total melting time of PCM.‎ Tube diameter variation can cause negligible change on melting time in comparison with coil ‎diameter.‎ Temperature distribution in the vertical direction improves for larger coil diameters.‎ Abstract: Since new technology in residential buildings encourages the implementation PCM heat storage systems and as far as larger heat transfer surface can be provided using spiral coil heat storage systems, it is aimed to introduce this enhancement via a numerical study. In this ‎study, spiral coil tube is considered in a shell and tube heat storage unit and numerical ‎simulations are performed to predict the effect of geometrical and operational parameters such as spiral coil ‎diameter, tube diameter, HTF mass flow rate and HTF inlet temperature on heat transfer characteristics and thermal behavior of Paraffin ‎RT50 as phase change material during melting process in the shell and spiral coil tube heat ‎exchanger while HTF flows inside the tube and PCM fill the space between shell and tube. ‎Simulation results showed that spiral coil diameter plays an important role in melting process ‎and heat transfer procedure. By increasing spiral coil diameter from 50 mm to 70 mm, total ‎melting time will reduce up to 71.4%. In contrast, tube diameter has little effect on melting ‎process. It is indicated that for larger spiral coil diameter, increasing tube diameter has a ‎reverse impact on reduction of total melting time.‎